A Stylistic Analysis of Chimamanda Adichie’s Language Use in The Thing Around Your Neck (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2024)
This research centers on the language and style of Chimamanda Adichie's The Thing Around Your Neck. The aim is to discover how she manipulated language to pass her messages across to the readers with her different styles. Past studies on style and stylistics focused their analysis on the old methods where every literary and linguistic works were analysed from phonological, morphological, semantic and syntactic level. However, this present study had opened another vista for the analysis of works based on the principles of cultural identity theory alongside investigating several linguistic aspects like conversational framing, linguistic appositioning and discourse implicature which were not accounted for in previous research. Because this was a library-based study, data was gathered through a close critical reading of the two novels and extracting words, phrases and sentences from secondary sources relevant to the study. The analysis of the sampled data for this study was purposively sampled. Cultural identity theory formed the theoretical framework for this study. The findings show that the writer's languages were interwoven with Igbo phrases and sentences, which could be deciphered by non-Igbo speaking and western readers through the usage of general lexical context. Her languages are geared primarily towards promoting her culture and tradition, as observed from the analyzed data. However, these languages should be effectively translated either directly or contextually to enhance the flow of meaning for non-native speakers of those languages.
Keywords: Style; Stylistics; Transliteration; Language; Culture